Papua New Guinea Agriculture, Food and Nutrition Policy Support Program - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
In Papua New Guinea (PNG), more than 80 percent of the population depends on agriculture for their livelihoods, with a vast majority working as smallholder farmers. Recognizing the need to revitalize and transform its agriculture sector, PNG’s government has set ambitious growth targets for agricultural exports and domestic agricultural production. It considers strategic investment in agricultural research and food security fundamental to overall economic growth and structural transformation.